PERAN RASIO KEUANGAN SEBAGAI ALAT ANALISI UNTUK MENDETEKSI KECURANGAN PELAPORAN KEUANGAN - Ramadhan, Istiqlal; Laksito, Herry (Diponegoro Journal of Accounting, 2019)
Fraudulent practice in the financial report has resulted in the decrease of reliability in the financial report so that the attached information became misleading to financial report user and resulting in a decrease of trust toward financial report. A method that can be the reference to rate financial report’s performance is financial ratios. Financial ratios can represent the company's performance and become a trigger factor for management to commit fraud. Then, by carefully paying attention to the trigger factors, it is expected to be able to detect fraud as soon as possible. Therefore, this study is aiming to prove that financial leverage ratio, profitability ratio, asset composition ratio, liquidity ratio, and capital turnover ratio affect fraudulent financial reporting.The population used in this study are all registered companies in Indonesia Stock Exchange (BEI) throughout 2010-2016. Using a purposive sampling method, the number of samples used are 62 companies. It consists of 31 fraud companies, as obtained from the database of sanctioned misstatement of financial reporting issued by OJK throughout 2010-2016 period and 31 non-fraud companies of the same size as determined under OJK Regulation No. 04 about Statement of Registration in the Public Offering and Capital Addition by Granting Right of Priority Effect by Companies with Small-Scale Assets or Companies with Medium-Scale Assets. Another source is from sanctioned warning category VIII.G.7 issued by OJK about proved fraud companies in presenting the financial report. Method of analysis used in this study is logistic regression analysis to examine the research hypothesis.The results of this study indicate that the financial leverage ratio and profitability affect positively toward the possibility of having fraudulent practice in the financial report. Meanwhile, asset composition ratio, liquidity, and capital turnover have a negative effect on the possibility of a fraudulent financial report.